Le douaire en droit coutumier ou la déviation d'une institution - Castelli, Mireille (Les Cahiers de droit, 1979)
Dower was a rather peculiar institution of the old French customary law that, according to some, still subsists in modern Quebec law. At first blush, dower seems to be in complete opposition to the main thrust of old French law, whose primary- concern for the protection of lineage allowed hardly any right to be created in favour of spouses. Indeed, dower granted to the wife important rights, bearing on the husband's biens propres, i.e. property coming from his lineage or not included in the community and therefore normally entitled to the strictest protection. The wife's rights consisted in a usufruct on one-half of the husband's bien propres. Considering both the basis and the extent of those rights, therefore, dower appears as a most unusual provision in favour of the wife. The advantages of dower were, however, more apparent than real. This comes out clearly when one examines the rights of children under the dower, as well as the manner in which the institution was transformed. Dower then appears as a mere reduction of the rights of full ownership previously vested in the wife. Such reduction favoured the children, who emerged as the main beneficiaries of dower. They were the owners of the property upon which bore the wife's usufruct. And their rights were safeguarded as against every other party, including their mother and father, as well as the latter's creditors. The history of dower therefore illustrates the manner in which legal institutions may be transformed to suit changing ideas and mores.